PENGARUH SYARIAH DALAM PRAKTEK BISNIS MIKRO DAN KECIL - A Natsir, Andi Fadhilah; Saeni, Jufri (Indonesian Journal of Shariah and Justice, 2023)
This article aims to analyze the influence of sharia in micro and small business practices. The method used is library research, where the data collection is by understanding and examining and studying the theories contained in books, articles, journals, and previous research results as a reference that is relevant between the theory that is recognized with the theme raised. The result of this paper is that the influence of sharia in micro and small business practices is to provide dedication in the form of services and products that provide benefits to many people and stay away from goods that provide mudharat. Then in terms of price, it is also regulated so as not to make it difficult for consumers so that the products and services offered are commensurate with the price offered.